2022
DOI: 10.3390/molecules27238403
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Ion-Based Switch-on Fluorescence-Sensing Probes for the Detection of Tetracycline

Abstract: Tetracycline (TC) is an antibiotic that has been widely used in the animal husbandry. Thus, TC residues may be found in animal products. Developing simple and sensitive methods for rapid screening of TC in complex samples is of great importance. Herein, we demonstrate a fluorescence-sensing method using Zn2+ as sensing probes for the detection of TC. Although TC can emit fluorescence under the excitation of ultraviolet light, its fluorescence is weak because of dynamic intramolecular rotations, leading to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…First, a 15 µL 100 nmol/L ssDNA solution was mixed with TC solution at varying concentrations (5,8,17,20,25,30, and 35 ng/mL) and incubated at 37 • C for 30 min. Second, 1.5 µL of 100 µg/mL oxSWCNHs was added and allowed to react at room temperature for 10 min.…”
Section: Tc Detection With Oxswcnhs-fam Aptasensormentioning
confidence: 99%
“…First, a 15 µL 100 nmol/L ssDNA solution was mixed with TC solution at varying concentrations (5,8,17,20,25,30, and 35 ng/mL) and incubated at 37 • C for 30 min. Second, 1.5 µL of 100 µg/mL oxSWCNHs was added and allowed to react at room temperature for 10 min.…”
Section: Tc Detection With Oxswcnhs-fam Aptasensormentioning
confidence: 99%
“…Chen et al reported RIM of TC in coordination with Zn 2+ -tris(hydroxymethyl)amino-methane conjugate ( B11 ) which causes the turn-on of green-yellow fluorescence. 188 In another example, Li and Pu et al prepared a ratiometric fluorescence probe based on AIE-active lumino-Eu 3+ complex ( B12 ), which changes fluorescence colour from blue to red when TC was added in the presence of citrate as a chelating agent. 189 This quenching mechanism is attributed to IFE caused by TC which quenches 453 nm emission of lumino-Eu 3+ complex at the expense of 626 nm Eu 3+ emission.…”
Section: Sensing Of Drug Moleculesmentioning
confidence: 99%
“…In recent years, widespread research has been undertaken on the detection of metal ions [ 1 , 2 , 3 , 4 , 5 ] and inorganic anions [ 6 , 7 , 8 , 9 ], particularly within the development of selective ion probes, which has more generally become a popular topic in scientific research. Zn 2+ is the second most common element in the human body, after iron, and not only plays an important role in protein structure, catalysis, transcription, and regulation, but is also closely associated with nerve signal transmission, enzyme regulation, and gene expression [ 10 ].…”
Section: Introductionmentioning
confidence: 99%